Molecular and biochemical evidence on the protective effects of quercetin in isoproterenol-induced acute myocardial injury in rats - Kumar M.; Kasala E.R.; Bodduluru L.N.; Kumar V.; Lahkar M. (My University, 2025)
Cardioprotection represents one of the most important and realistic aspects of preventive therapy today. Quercetin, a naturally occurring dietary flavone, has been studied extensively for its antioxidant properties. The objective of present study is to find out the cardioprotective activity and to explore the underlying mechanisms of quercetin pretreatment (50 mg/kg body weight, orally) for 14 days against isoproterenol (ISO; 100 mg/kg body weight, subcutaneously) induced myocardial infarction in Wistar rats. Cardiac diagnostic markers, oxidative stress, inflammatory cytokines, histopathology along with gene expression analysis of calpain 1 and 2 were carried out in experimental rats. Quercetin pretreatment showed protective effects on heart by significantly attenuating the ISO-induced oxidative stress, inflammation, protecting heart architecture, and by downregulation of the expression of calpain. Overall, these findings revealed the cardio-protective potential of quercetin and its mechanism of action against ISO-induced MI in rats. © 2016 Wiley Periodicals, Inc.